1987
DOI: 10.1002/ps.2780190107
|View full text |Cite
|
Sign up to set email alerts
|

Permethrin treatments in canadian forests. Part 2: Impact on stream invertebrates

Abstract: A series of experiments was conducted between 1977 and 1981 to evaluate the effects of aerially applied permethrin on forest stream invertebrates. All permethrin applications to forest streams resulted in large drift increases, and most produced measurable reductions in benthos density. Recovery of benthic fauna following the various permethrin applications was apparent from 1 to 18 months post‐spray. In double‐application experiments, the second treatments reduced benthos density to a point at which recovery … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

1987
1987
2005
2005

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…The idea that stream macroinvertebrate communities are highly resilient to single pulses of insecticides is supported by the findings of Sibley et al [10], who exposed a Canadian headwater stream to a single, 15-min pulse exposure (16 g L Ϫ1 ) of the pyrethroid permethrin. However, several repeated exposures [29] or prolonged exposure [30] might exclude species for as long as 18 months after exposure, as observed by Kreutzweiser and Kingsbury [29]. However, several repeated exposures [29] or prolonged exposure [30] might exclude species for as long as 18 months after exposure, as observed by Kreutzweiser and Kingsbury [29].…”
Section: Benthic Densities Of Macroinvertebratesmentioning
confidence: 95%
See 1 more Smart Citation
“…The idea that stream macroinvertebrate communities are highly resilient to single pulses of insecticides is supported by the findings of Sibley et al [10], who exposed a Canadian headwater stream to a single, 15-min pulse exposure (16 g L Ϫ1 ) of the pyrethroid permethrin. However, several repeated exposures [29] or prolonged exposure [30] might exclude species for as long as 18 months after exposure, as observed by Kreutzweiser and Kingsbury [29]. However, several repeated exposures [29] or prolonged exposure [30] might exclude species for as long as 18 months after exposure, as observed by Kreutzweiser and Kingsbury [29].…”
Section: Benthic Densities Of Macroinvertebratesmentioning
confidence: 95%
“…Six weeks after exposure, the macroinvertebrate community had recovered to pre-exposed levels. However, several repeated exposures [29] or prolonged exposure [30] might exclude species for as long as 18 months after exposure, as observed by Kreutzweiser and Kingsbury [29].…”
Section: Benthic Densities Of Macroinvertebratesmentioning
confidence: 95%
“…Samples fortified at a level of 25 ng L −1 yielded a mean ± standard deviation of 23 ± 2.9 ng L −1 for chlorpyrifos ( N = 218) and 24 ± 1.9 ng L −1 for diazinon ( N = 188). ( 26 ) Compared to the variation in effects data discussed in the following section, analytical variability was negligible in the key threshold concentrations used in the RADAR analysis (22–177 ng L −1 ). Consequently, only the reported point estimates of concentration were utilized in the assessment.…”
Section: Uncertainity and Variability Analysismentioning
confidence: 88%
“…Analysis of additional samples collected using the U.S. GS Equal Width Increment protocol ( 25 ) indicated that the autosampler single‐point intakes also were representative of the spatial concentration profile across the stream channel in this well‐mixed stream. ( 26 ) Sampling error appears to be minimal.…”
Section: Uncertainity and Variability Analysismentioning
confidence: 95%
“…Although these pyrethroid insecticides are extremely toxic to aquatic invertebrates and vertebrates, their use for aerial application could be limited to sites where no aquatic systems are present or where they could be effectively buffered from the effects of the treatment Kreutzweiser and Kingsbury 1987). A petition to register permethrin as a ground spray against Z. canadensis has been filed in Canada.…”
Section: (A) Windows Of Opportunity For Interventionmentioning
confidence: 99%